A Non-Lethal Electric Shock Generator with Wireless Control Function. (April 2020) - Yang, Chunxia; Wan, Gang; Liu, Jian; Zhang, Wenxuan; Tian, Hui; Li, Zhenxiao; Jin, Yong; Li, Baoming
Abstract: A Non-lethal electric shock generator is presented and tested. This non-lethal electric shock generator without trail wires, is different from Taser series stun guns or Husha TX series electric shock guns which all have trail wires. And the intensity of electric shock can be adjusted by remote control device according to the status of the target. This no-lethal electric shock generator extends the range of application of electric shock from about 9 meters to 30 meters. The manner of using electric shocks of single intensity is also changed by telecontrol adjustment. It can provide electric shocks of different intensities for different conditions, such as different distances from special electrodes to targets, different targets with different clothes and different height or weight. Basic functions of the non-lethal electric shock generator are tested. Results show that the prototype projectile can be launched from a barrel stably, and the flight range is over 30 meters. When it captured the target, it can be triggered via the telecontrol adjustment. The prototype projectile can support a series of pulses at a rate of 20 r/s with the peak voltage of 30kV.